Role playing game as a learning media: case study on education industry course - Muhammad Dominique Mendoza; Olnes Yosefa Hutajulu; Reni Rahmadani; Fevi Rahmawati Suwanto; Ishaq Matondang; Ressy Dwitias Sari (Jurnal Info Sains : Informatika dan Sains, 2024)
Paradoxically, the current level of enthusiasm among the younger generation in studying the education industry is low. This phenomenon can be attributed to multiple factors, including the rapid spread of globalization, which has sparked a heightened interest among the younger generation in acquiring technological knowledge. Researchers employed the Game Development Life Cycle (GDLC) approach, consisting of six stages: initiation, pre-production, production, testing, beta, and release. Testing using the black-box method on 12 modules revealed that all modules performed flawlessly without any issues. Testing of the beta version of the game involved 62 testers who were instructed to play the game and complete a questionnaire. The findings were positive, with an average total score of 4.51 for the game elements. The gaming system performed well during testing, indicating its potential to be well-received by beta testers and users, as well as its ability to enhance students' learning motivation.